(untitled) (Politeja, 2022)
The present study examines the directions of Russia’s demographic policy in the context of the accumulating challenges in this area and analyzes the results of this policy as well as the prospects for further development of the situation. The development of the Russian population since the Soviet era shows a steady tendency: the number of births in the regions inhabited by ethnic Russians is seriously declining, with an increase in regions inhabited by ethnic groups traditionally professing Islam. Remedial steps were already taken in the 1990s, but the turning point was 2007, when the regulations related to the introduction of Maternity Capital entered into force. Another important step was the initiation of the national project “Demography”, which significantly increased social assistance not only for families with children, but also for the older generation. The Maternity Capital policy positively correlates with the increase in births in the following years, however, after the Crimean events, the positive trend collapses and the birth rate shows a clear decreasing tendency. Undoubtedly, success has been achieved in extending life expectancy. The tendency of a definitely positive net migration is not retreating either. The long-term effect of these processes is the aging of the Russian society and the change of the ethnic structure towards an increase in the number of the country’s Muslim population. A significant population growth is observable in metropolitan cities as well as in tourist and agricultural regions of the South-West while peripheral and rural areas are dying out. The fact that despite legislative and organizational efforts the number of the Federation’s inhabitants is falling indicates the limited nature of social policies aimed at manual control of social processes.